(untitled) (Forum Penelitian Agro Ekonomi, 2016)
English The milk consumption trend in Indonesia has been growing since 1969, which is thought to be basis for developing existing dairy industry. The paper attempts to review the present picture of dairy industry in Indonesia. The study is based on the secondary data and information obtained from relevant sources. The paper concludes that the dairy industry is heavily regulated. The fluid milk production is characterized by small-size operations on one hand, and the processing side is dominated by quite a few large scale corporations on the other hand. The fresh milk market is relatively more competitive than the dairy products market. Some dairy products are produced under oligopolistic or even monopolistic factories. Although the fresh milk production is organized under co-operative system, its role is weak relative to the factories’ role. The role of co-operative will further dwindle when the GATT/WTO agreement becomes in effect. Both price and income elasticities of dairy products seem to be elastic. Thus, as income per capita improves, the demand for dairy products are expected to increase. This will lead to higher growth of imports. To maintain consumers’ satisfaction, trade and investment policies in milk factories needs to be relaxed to stimulate fair competition. ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Indonesian Konsumsi susu di Indonesia cenderung meningkat sejak tahun 1969, yang menjadi dasar pengembangan industri persusuan saat ini. Makalah ini merupakan tinjauan dari dari gambaran keadaan industri persusuan di Indonesia. Penelitian ini didasarkan pada data sekunder dan informasi yang dikumpulkan dari lembaga instansi dan sumber-sumber terkait dengan persusuan nasional. Makalah menyimpulkan bahwa industri persusuan sarat dengan perlindungan pemerintah. Bidang budidaya dan produksi susu segar dicirikan oleh usaha skala kecil yang jumlahnya banyak sementara bidang pengolahan (IPS) dikuasai oleh perusahaan besar yang jumlahnya sangat sedikit. Pasar susu segar lebih bersaing daripada pasar produk susu. Bahkan beberapa produk diproduksi oleh perusahaan yang oligopolistik atau bahkan monopolistik. Walaupun produksi susu segar diorganisasikan dalam bentuk koperasi, peranannya sangat lemah dibandingkan dengan peranan IPS. Peranan koperasi ini akan semakin melemah nanti, manakala aturan-aturan GATT/WTO akan diterapakan di kemudian hari. Nilai elastisitas permintaan harga dan pendapatan produk susu akan meningkat pula. Hal ini akan menyebabkan peningkatan impor produk susu. Untuk memelihara kepuasan konsumen di dalam negeri, maka beberap kebijakan perdagangan dan investasi dalam pengolahan susu perlu dilonggarkan agar tercipta persaingan yang sehat.